Bismuth sodium titanate-barium titanate-barium zirconate titanate relaxor ferroelectric ceramics with high recoverable energy storage density. Issue 18 (15th September 2022) - Chen, Yanqin; Fan, Huiqing; Hou, Dingwei; Jia, Yuxin; Zhang, Ao; Wang, Weijia
Abstract: Lead-free relaxor ferroelectric ceramics are attracting attention due to their fast charge/discharge and environmentally friendly properties. In this work, the bismuth sodium titanate-barium titanate-barium zirconate titanate [(0.94Bi0 · 51 Na0 · 47 TiO3 -0.06BaTiO3 ) -x BaZr0.3 Ti0 · 7 O3, abbreviated as BNBT-100 x BZT] relaxor ferroelectric ceramics were synthesized by the solid-state reaction technique. The microstructure, energy storage properties, and conductivity mechanism of BNBT-100 x BZT were analyzed as the barium zirconate titanate doping content changed. All BNBT-100 x BZT have a single perovskite structure by XRD. The BNBT-5BZT ceramics was found to be tetragonal by Rietveld refinement. Moreover, the doping of BZT is beneficial to optimize the breakdown strength (BDS). Owing to the higher BDS, an effective energy storage density of 1.457 J/cm 3 was obtained under 122 kV/cm in BNBT-5BZT with an energy storage efficiency ( η ) of 81.9%. In addition, BNBT-5BZT has outstanding temperature and cycling stability. The results indicate that BNBT-5BZT ceramics is excellent candidates for energy storage devices. Graphical abstract: A new relaxor ferroelectric bismuth sodium titanate-barium titanate-barium zirconate titanate synthesized with a tetragonal phase shows an energy storage density of 1.457 J/cm 3 at 122 kV/cm and energy storage efficiency of 81.9%. Image 1